Analysis of domain identification and authentication - Mylkovsky, D.V.; Oreshko, Z.A.; Potii, A.V. (Radiotekhnika, 2017)
The work is devoted to the analysis of the terminology of authentication and identification, the standards of the USA, the European Union, international standards ISO / IEC, recommendations of the ITU, normative documents of Ukraine and national standards, including harmonized with international ones.